Development of a Water Cycle E-module Assisted by a Flipbook Application for 5th Grade Elementary School Students - Atiyah, Dwi Nastiti; Rufi’i, Rufi’i; Suhari, Suhari (Universitas Sebelas Maret, 2025)
This study aims to develop a water cycle E-module assisted by the Flipflop for fifth grade elementary school students. The use of technology not only provides flexibility during the learning process but also fosters active participation and enhances student interactivity, thereby creating a more meaningful learning experience. The research method used is research and development (R&D) with ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data collection techniques used in this study were observation, interviews, and questionnaires. Data collection instruments consist of observation sheets, interview guidelines, and student response questionnaires. The results of the study showed that the developed water cycle e-module was valid and practical to use. The research results from media experts obtained a percentage of 94.2% and material experts 98.5% which fell into the very valid category. Furthermore, in terms of practicality, the teacher obtained a result of 88.2% in the very practical category and when the small-scale trial obtained a percentage of 73.2% in the practical category and the limited-scale trial obtained a percentage of 80.7% in the practical category.